Settling up in CEO compensation: The impact of divestiture intensity and contextual factors in refocusing firms - Pathak, Seemantini; Hoskisson, Robert E.; Johnson, Richard A. (Strategic Management Journal, 2014)
We examine the relationship between strategic change and CEO compensation by studying how a firm's refocusing program influences CEO compensation after completing the change. We contribute to the ‘settling up’ literature by arguing that strategic change is often uncertain for both the CEO and the board of directors responsible for executive compensation. As such the firm is likely to settle up with the CEO by paying for compensation risk and effort undertaken during refocusing after the extent and impact of strategic change are better known. We find that refocusing intensity is positively related to post‐refocusing CEO total compensation, suggesting that ‘settling up’ through post hoc compensation is an important factor in strategic change. We also find that prior firm performance, governance structure and industry dynamism are important moderators of this relationship . © 2013 John Wiley & Sons, Ltd.